47 Views of healthcare professionals on issues around ductal carcinoma in situ detected through an expanded mammography screening program. (4th December 2019) - Hersch, Jolyn; Jansen, Jesse; Nickel, Brooke; Rutherford, Claudia; Houssami, Nehmat; Barratt, Alexandra; Saunders, Christobel; Spillane, Andrew; Stuart, Kirsty; Wylie, Elizabeth; Robertson, Geraldine; McCaffery, Kirsten
Abstract : Introduction: The incidence of ductal carcinoma in situ (DCIS) has increased greatly since the introduction of organised breast screening. Because DCIS encompasses a spectrum of disease, including some indolent lesions that may not progress, there is growing concern about overdiagnosis and overtreatment. Women aged 70–74 years are included in the expanded age range now targeted for population screening in Australia, and this group may differ from younger women in terms of potential for benefit and harm. We aimed to understand healthcare professionals' views about DCIS. Methods: Doctors and nurses working with DCIS patients in diverse settings around Australia and New Zealand were recruited via professional organisations and contacts. We conducted semi-structured telephone interviews with 26 healthcare professionals (10 breast surgeons, 6 radiation oncologists, 3 breast physicians, 7 breast care nurses). Topics included current practice and future directions for managing DCIS, issues around patient communication, and benefits and harms of screening women over 70. Interviews were audio-recorded, transcribed, and analysed thematically. Results: Many participants felt the screening age extension was justified because life expectancy has increased. They suggested that older women often interpret their screening invitations stopping as an indication that they are no longer at risk of breast cancer. On the other hand, many clinicians believed that continuation of screening should depend on individual life expectancy given the risk of harm, for example through overdiagnosis and overtreatment of low-grade DCIS among older women in poor health. Some participants emphasised that women should be informed about potential consequences of screening, including benefits and harms, and involved in deciding whether to be screened. Discussion: Doctors and nurses who work with DCIS patients offer a valuable perspective on current issues around the detection and management of DCIS. We will discuss the key findings and their implications for future research, screening and clinical practice.